The SITARI (independent non-communicable disease screening) information system in the accuracy and speed of screening for non-communicable diseases in women of childbearing age - Bekti Putri Harwijayanti; Aulia Fatmayanti (Jurnal Kesehatan Ibu dan Anak, 2022)
Deaths from Non-Communicable Diseases (NCDs) are the most deaths in various countries. Its prevalence reaches 71% of deaths globally, where 77% of NCD deaths occur in lower-to-middle countries. NCDs detection/screening and treatment, palliative care, are the solution components of NCDs management. Implementation of the Independent Non-Communicable Diseases Screening/Skrining Penyakit Tidak Menular Mandiri (SITARI) allows women of childbearing age (WCA) to screen for non-communicable diseases affecting to maternal health independently. The purpose was to determine the effect of the SITARI information system (independent non-communicable disease screening) on the completeness and speed of screening for NCDs. The result showed that the significance value is 0.000 (p, <0.05). There is a difference in the completeness of the data between WCA who use SITARI and WCA who do not use SITARI with a mean difference of 26.09. There is a significance value of 0.000 (p, <0.05), meaning that there is a difference in screening speed for WCA who use SITARI and WCA who do not use SITARI with a mean difference of 10.80. This proves that the completeness and speed of NCDs screening using SITARI are better than those not using it.